Enhancement of Biogas production and organic reduction of sludge by different pre-treatment processes - S. Almukhtar, Riyadh; A. Alwasiti, Asawer; T. Naser, Mohammed (Iraqi Journal of Chemical and Petroleum Engineering, 2012)
Anaerobic digestion (AD) is the most common process for dealing with primary and secondary wastewater sludge. In the present work, four pre-treatment methods (ultrasonic, chemical, thermal, and thermo-chemical) are investigated in Al-Rustumya Wastewater Treatment plant in order to find their effect on biogas production and volatile solid removal efficiency during anaerobic digestion. Two frequencies of ultrasonic wave were used 30 KHz and 50 KHz during the pre-treatment. Sodium hydroxide was added in different amounts to give three pH values of 9, 10 and 11 in chemical pre-treating processes. The sludge was heated at 60oC and 80oC through thermal pre-treatment experiment. Also, the sludge was treated thermo-chemically at 80 oC and pH 11 prior to anaerobic digestion. Maximum biogas production (6009 ml) was obtained at ultrasonic pre-treatment method with 30 kHz. The volumetric ratio of produced biogas to the initial volume of sludge is about 4:1.